Harnessing The Power of Instagram: Key Factors Influencing Followers' Visit Intentions to Cultural Destinations - Daru Putri Kusumaningtyas; Raya Sulistyowati; Daniel Pungkas Prastia Wibowo; Sajiwo Tri Prakoso; Rizka Zakiah; Fitra Dila Lestari (Journal of Business and Behavioural Entrepreneurship, 2025)
This study explores the influence of Museum Generated Content (MGC) on Instagram on perceptions of information quality, customer service, and intention to visit Sonobudoyo Museum. Through quantitative methods and SEM PLS analysis, this study identified that accurate, relevant, and responsive museum content on social media has a significant impact on forming positive perceptions and increasing intention to visit. By involving 206 respondents who are followers of museum Instagram accounts, this study provides in-depth insights into the role of social media in the cultural tourism sector, especially in attracting the interest of the younger generation who are increasingly dependent on digital information in making travel decisions. This study also fills the literature gap regarding the impact of MGC on social media, making an important contribution to the academic understanding of digital marketing in the museum industry. The results of the study Museum Generated Content (MGC) on Instagram has a positive and significant influence on perceptions of information quality, perceptions of service, and intention to visit Sonobudoyo Museum. Accurate, complete, and up-to-date content, as well as responsive and sincere service, have been shown to play an important role in building positive perceptions and increasing intention to visit.